Titos Jugoslawien – der kommunistische Alliierte von Prag und Washington - Jakovina, Tvrtko (Array, 2008)
Based on the Yugoslav diplomatic and Party dispatches, American, British and a few Russian documents, author tried to describe relations between Yugoslavia and Czechoslovakia during 1968. The exchanges between Prague and Belgrade are put in the larger context of the overall relations between the West and the East. The author dwells on the ideological differences between Moscow and Belgrade as well as on the special position of Tito’ s Yugoslavia in the Cold War.